Effect of globalization on Technical Efficiency in the regional context of Colombia (2019)
The 1980s showed strong changes and adjustments in economic models in Latin America, after the exhaustion of the import substitution industrialization model. In those years, the majority of countries in the region registered strong macroeconomic imbalances that led to important economic adjustments. After the exhaustion of this model, countries moved towards economic paradigms of international openness economy. Colombia in particular started this process in the 1990s, which led to greater interaction with other economies in the region. This undoubtedly has had influence on the use of production factors, therefore the aim of this research is to show how this has been conducted, by obtaining an indicator of technical efficiency for Colombia and the countries it shares geographical border with. The methodology used is that of stochastic boundaries. The main findings are that there is still a wide possibility of improving technical efficiency of countries considered in the study and that economic openness has contributed to improve the use of productive factors, even for Colombia.